Preparation of a novel high-strength polyzwitterionic liquid hydrogel and application in catalysis. Issue 122 (24th November 2015) - He, Xiaoyan; Qiang, Shenglu; Liu, Zhirong; Wang, Meng; Yang, Wu
Abstract : A new polymeric hydrogel P(PVIS–AA) based on zwitterionic liquids (1-propyl-3-vinyl imidazole sulfonate) (PVIS) and acrylic acid (AA) was prepared by free-radical polymerization. Abstract : A new polymeric hydrogel P(PVIS–AA) based on zwitterionic liquids (1-propyl-3-vinyl imidazole sulfonate) (PVIS) and acrylic acid (AA) was prepared by free-radical polymerization. The resulting three-dimensional (3D) networks can serve as nano-reactors for the production of small size and highly stable palladium nanoparticles by in situ reduction of PdCl6 2− with sodium borohydride (NaBH4 ) as a reducing agent. To get enough mechanical strength, ferric (Fe 3+ ) was used to form the second crosslinking. The as-prepared hybrid hydrogel (P(PVIS–AA)/Pd@Fe 3+ ) was successfully confirmed by means of Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX), field emission scanning electron microscopy (FESEM), an electrical universal material testing machine, transmission electron microscopy (TEM) and thermogravimetric analysis (TGA), and then tested to catalyze the reduction of 4-nitrophenol. The catalytic results indicate that within 6 min, 4-nitrophenol with an initial concentration of 5 mM can be reduced completely, in addition, the mechanically strengthened P(PVIS–AA)/Pd@Fe 3+ hydrogel shows excellent reusability for five successive cycles, with no appreciable decrease in the catalytic effects.